Customer brand identification, affective commitment, customer satisfaction, and brand trust as antecedents of customer behavioral intention of loyalty: An empirical study in the hospitality sector - Rather, R. A.; Tehseen, Shehnaz *; Itoo, M. H.; Parrey, S. H. (Taylor & Francis, 2019)
The current study presents an integrated model that explores how customer brand identification (CBI), affective commitment, customer satisfaction, and brand trust influence the development of customer behavioral intention of loyalty (CBIL) in the hospitality sector. The underpinning theories of this study are social identity theory and relationship marketing theory. Data were collected in the form of a survey from 345 customers staying at different hotels across six cities in India. The data were analyzed by using confirmatory factor analysis, followed by structural equation modeling. The findings illustrated that the influence of CBI on CBIL is direct as well as mediated by affective commitment, customer satisfaction, and brand trust. The latter three constructs were also direct predictors of CBIL while the influence of customer satisfaction and brand trust on CBIL was found to be mediated by affective commitment as well. These matters have received little attention in marketing generally and hospitality research particularly, and knowledge of the proposed relationships may lead to further research on this topic.